2008
DOI: 10.1093/ajcn/87.3.558
|View full text |Cite
|
Sign up to set email alerts
|

Do trans fatty acids from industrially produced sources and from natural sources have the same effect on cardiovascular disease risk factors in healthy subjects? Results of the trans Fatty Acids Collaboration (TRANSFACT) study

Abstract: This study shows that TFAs from industrially produced and from natural sources have different effects on CVD risk factors in women. The HDL cholesterol-lowering property of TFAs seems to be specific to industrial sources. However, it is difficult in the present study to draw a conclusion about the effect of TFAs from either source on absolute CVD risk in these normolipidemic subjects. The mechanism underlying the observed sex- and isomer-specific effects warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
166
3
13

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(185 citation statements)
references
References 38 publications
3
166
3
13
Order By: Relevance
“…A third intervention study suggested that R-TFA intake could affect women and men differently. Among women, both high-density lipoprotein-cholesterol and low-density lipoprotein-cholesterol were higher after intake of 5 E% (B11-12 g/day) R-TFA compared with equivalent intakes of IP-TFA, whereas only minor differences were observed in men (Chardigny et al, 2008). In accordance, no significant difference between the effects of TFA from the two sources on the low-density lipoprotein/high-density lipoproteincholesterol ratio (P ¼ 0.37) was found in a recent quantitative review (Brouwer et al, 2010), which compiled the evidence from 29 and 6 treatments with IP-TFA and R-TFA intake, respectively.…”
Section: Nhsmentioning
confidence: 81%
“…A third intervention study suggested that R-TFA intake could affect women and men differently. Among women, both high-density lipoprotein-cholesterol and low-density lipoprotein-cholesterol were higher after intake of 5 E% (B11-12 g/day) R-TFA compared with equivalent intakes of IP-TFA, whereas only minor differences were observed in men (Chardigny et al, 2008). In accordance, no significant difference between the effects of TFA from the two sources on the low-density lipoprotein/high-density lipoproteincholesterol ratio (P ¼ 0.37) was found in a recent quantitative review (Brouwer et al, 2010), which compiled the evidence from 29 and 6 treatments with IP-TFA and R-TFA intake, respectively.…”
Section: Nhsmentioning
confidence: 81%
“…The first output from the TRANSFACT study showed that industrial and ruminant TFA have different effects on CVD risk factors. Only industrial TFA lowered HDLcholesterol, although the responses were greater in women than in men (Chardigny et al, 2008). Overall, there appears to be little if any increased risk of CVD from consumption of ruminant TFA, at least at current intakes.…”
Section: Milk and Dairy Products As Sources Of Trans-fatty Acids (Tfa)mentioning
confidence: 82%
“…Such a comparison was attempted in the 'Transfact' trial, which fed healthy human volunteers diets containing 5% of energy as TFA from either PHVO or dairy fat. Somewhat surprisingly, only minor changes were seen in plasma lipoproteins with both sources of TFA compared with baseline diet, and the authors concluded that no conclusions could be drawn 'about the effect of TFAs from either source on absolute CVD risk in these normolipidemic subjects' (Chardigny et al, 2008). In a recent metaanalysis, Bendsen et al (2011) compared the impact of industrial (PHVO) and ruminant TFA on risk of CHD.…”
Section: Tfa and Cardiovascular Riskmentioning
confidence: 99%